Evaluation of the ability and accuracy of dental students in diagnosing proximal caries depth in bite-wing radiography - Elham Romoozi, Mahsa Nili, Hossein Akbari, hamidreza Maleki (Drugs and Cell Therapies in Hematology, 2021)
Introduction: Tooth decay is the most prevalent chronic human disease in the world and the dentist acquires the ability to diagnose it in the approved manner during training courses. Radiography is used to diagnose and treat this issue. Thus, mastering the diagnosis of caries from radiographic images can play an imperative role in providing a suitable treatment plan. Methods: In this cross-sectional study, 40 bite-wing radiographic images (304 interdental surfaces) were examined to diagnose proximal caries and determine its depth by students of the last two years and 2 professors of the Dentistry Faculty of Kashan to determine the gold standard. In case of disagreement, the images were referred to a third specialist. Data were collected in SPSS 22 software and analyzed by Kappa test. Results: The diagnostic sensitivity of proximal tooth decay by students in the last two years was 77.5%, its specificity was 75.4%, positive predictive value was 67.2%, negative predictive value was 83.7% and correct classification was 76.2%. The sensitivity of diagnosis of proximal dental caries by final year students was 74.9%, its specificity was 82.8%, positive predictive value was 74% and negative predictive value was 83.5%. The sensitivity of diagnosis of proximal dental caries by fifth-year students was 80.6%, its specificity was 66.6%, positive predictive value was 61.1% and negative predictive value was 84.1%. Conclusion: In this study, the diagnostic ability of final year students of the Dentistry Faculty of Kashan is evaluated concerning the presence or absence of relatively suitable caries and in the case of poor caries depth. Also, in this study, the diagnostic ability of fifth-year students of the Dentistry Faculty of Kashan is evaluated concerning the presence or absence of relatively suitable caries and in the case of poor caries depth.